EBF contains a novel zinc coordination motif and multiple dimerization and transcriptional activation domains. - Hagman, J (1995)
Early B cell factor (EBF) was identified and cloned as a transcription factor expressed specifically in B lymphocytes and adipocytes. This protein was also identified as olfactory factor 1 (Olf-1) in olfactory neurons. In this study, we analyzed the structural requirements for DNA binding, homodimerization and transcriptional activation by EBF. A carboxyl-terminal region, containing a repeat of alpha-helices related to the helix-loop-helix motif, is important for dimerization of EBF in solution and can confer dimerization upon a heterologous DNA binding protein. The amino-terminal DNA binding domain by itself is monomeric, but can mediate assembly of dimers on optimized and correctly spaced half-sites. Mutational analysis of the DNA binding domain of EBF indicated that a novel zinc coordination motif consisting of H-X3-C-X2-C-X5-C is important for DNA recognition. Deletion analysis and transfer of regions of EBF onto a heterologous DNA binding domain identified a serine/threonine-rich transcriptional activation domain. Moreover, the DNA binding domain of EBF can mediate transcriptional activation from optimized binding sites. Thus, EBF contains both a complex DNA binding domain that allows for dimerization and transcriptional activation, and additional dimerization and activation domains.